Bibliometric Analysis of Digital Marketing: Collaboration, Themes, and Opportunities - Sugiarti, Riski; Mujanah, Siti; Alif Fianto , Achmad Yanu (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2025)
This research examines the development of digital marketing scholarship through a bibliometric approach to identify collaboration patterns, dominant themes, and potential research opportunities. Data were collected from Google Scholar using Harzing’s Publish or Perish and analyzed with VOSviewer to map the evolution of digital marketing studies in recent years. The findings show that discussions in this field increasingly revolve around digital transformation, social media strategies, and their contribution to supporting micro, small, and medium enterprises (SMEs). Patterns of collaboration across authors and institutions demonstrate growing interdisciplinary engagement in digital marketing research. The analysis reveals four major thematic clusters: digital marketing strategies, SME empowerment, technological adaptation, and research development. These clusters highlight the role of technology and innovation in shaping new marketing models that enhance business–consumer interactions. The study also indicates several directions for future research, including digital consumer behavior, influencer involvement, and data-driven marketing decision-making. Overall, this bibliometric review offers a comprehensive overview of how digital marketing research continues to evolve and contribute to business growth, collaborative knowledge creation, and innovation in the digital era. Keywords: Digital Marketing; Collaboration; Themes; Opportunities; Bibliometric Analysis.